Multilocus species delimitation and phylogeny of the genus Calommata (Araneae, Atypidae) in southern China. (6th January 2022) - Li, Fan; Xu, Xin; Zhang, Zengtao; Liu, Fengxiang; Yang, Zizhong; Li, Daiqin
Abstract: Species delimitation is critical to our understanding of evolution, biodiversity, and conservation. However, delimiting species boundaries can be challenging, especially when intraspecific divergence is high (and interspecific divergence is low), and gene flow and incomplete lineage sorting are present. Mygalomorph spiders have become models for examining a variety of evolutionary and biogeographical questions. However, their extreme morphological homogeneity and high genetic structuring make delimiting mygalomorph species especially challenging. Integrative approaches to species delimitation, which combine multiple lines of evidence, have been used to infer the limits of many mygalomorph groups in an independent and reproducible way. Yet molecular species delimitation and phylogenetic relationships of the purseweb spider family Atypidae remain scarce. In this study, we explored the phylogeny and species delimitation of Calommata spiders from southern China using data sets including three mitochondrial ( COI, 16S, and 12S ) and two nuclear ( 28S, H3 ) markers. Our phylogenetic analyses yielded a well‐supported clade containing all southern Chinese Calommata and a sister relationship between C . signata and three new species within it. Based on the single‐locus and multilocus species delimitation analyses, we delimited four Calommata species from southern China: one known species ( C . signata ) and three new species ( C . yuanjiangica sp. n., C . hangzhica sp. n. and C . jinggangica sp. n.). This study thus provides a framework for determining the limits of C . signata sensu lato species and calls for further study of systematics and evolutionary relationships within Calommata and other atypid lineages.